Kesalahan dalam Menyelesaikan Soal Cerita Bangun Ruang Sisi Datar pada Siswa Kelas VIII MTs NW Senyiur Tahun Pelajaran 2023/2024 - Lestari, Susi; Laila Hayati; Ratna Yulistyaningisih; Sripatmi (Mataram University, 2024)
Newman’s error analysis is a method used to analyze student’s erors in solving mathematical story problems.In Newman’s analysis there are five stages, namely 1)reading errors, 2) comprehensior error, 3) transformation error, 4) procces skill error, 5) encoding errors. The purpose of this study is to describe the types of errors, made by students in solving story problems of flat-sided geometric shapes base on the Newman method in class VIII MTs NW Senyiur in the 2023/2024 academic year. The type of research used in the study is qualitative descriptive research. The research instruments used were story test question and interviews. The data analysis technique used in the analysis technique from Miles Huberman which consists of data reducation, data presentation, and drawing conclusions. The results of the study showed the percentage of errors madeby students in solving flat-sided geometricstory problems based on Newman’s error stages, namely reading errors of 17,5%, comprehension errors of 53,75%, transformation errors of 63,75%, process skill errors of 67,5%, and finally errors in writing the final answer (encoding errors) of 76,25%. The impact of this study is to help teachers identify where student’s errors are in solving mathematical story problems so that teachers can provide the right solution to minimize errors made by students.